Mink, SARS-CoV-2, and the Human-Animal Interface - Fenollar, Florence; Mediannikov, Oleg; Maurin, Max; Devaux, Christian; Colson, Philippe; Levasseur, Anthony; Fournier, Pierre-Edouard; Raoult, Didier (Frontiers in Microbiology, 2021)
Mink are small carnivores of the Mustelidae family. The American mink is the most common and was imported to Europe, Asia, and Latin America for breeding, as its fur is very popular. Denmark, the Netherlands, and China are the biggest producers of mink. Mink farms with a high population density in very small areas and a low level of genetic heterogeneity are places conducive to contagion. The mink’s receptor for SARS-CoV-2 is very similar to that of humans. Experimental models have shown the susceptibility of the ferret, another mustelid, to become infected with SARS-CoV-2 and to transmit it to other ferrets. On April 23, 2020, for the first time, an outbreak of SARS-CoV-2 in a mink farm was reported in the Netherlands. Since then, COVID-19 has reached numerous mink farms in the Netherlands, Denmark, United States, France, Greece, Italy, Spain, Sweden, Poland, Lithuania, and Canada. Not only do mink become infected from each other, but they are capable of infecting humans, including with virus variants that have mutated in mink. Human infection with variant mink viruses with spike mutations led to the culling in Denmark of all mink in the country. Several animals can be infected with SARS-CoV-2. However, anthropo-zoonotic outbreaks have only been reported in mink farms. The rapid spread of SARS-CoV-2 in mink farms raises questions regarding their potential role at the onset of the pandemic and the impact of mutants on viral fitness, contagiousness, pathogenicity, re-infections with different mutants, immunotherapy, and vaccine efficacy.